НОВІ МАЛОАПЕРТУРНІ ПЕРЕТВОРЮВАЧІ НА ОСНОВІ МАГНІТОСТРИКЦІЙНОГО ЕФЕКТУ ДЛЯ ДІАГНОСТИЧНИХ СИСТЕМ - Богачев, І.В.; Бабак, В.П.; Запорожець, А.O. (Інститут електродинаміки НАН України, Київ, 2022)
Small-aperture transducers based on the magnetostrictive effect for the emission and reception of signals in the ultrasonic range in solid materials have been developed. The article discusses their design features and specifications. Attention is paid to the features of the choice of materials, shapes, and geometrical dimensions of the excitation coil, damper, and magnet. Structural and electrical circuits of the developed transducers are given. Some design and technological solutions have been proposed that can increase the radiation power by 10 times, and resolution by 2-3 times, compared with existing analogs. The area of the radiating part of the sensor is from 0.07 to 0.2 mm2. Such transducers can be used in various diagnostic systems to detect defects in power equipment, aircraft products, industrial equipment, etc. References 22, figures 10, tables 4.